Assessment of clinical outcomes and prognostic factors following membrane peeling in idiopathic epiretinal membrane using EIFL staging system: an optical coherence tomography angiography analysis - Juan Li; Fangyuan Cheng; Zhaohui Li; Liang Wang (BMC Ophthalmology)
Abstract Background To evaluate the associations between anatomical changes and visual outcomes after membrane peeling in eyes with different stages of idiopathic epiretinal membrane (iERM) using optical coherence tomography angiography (OCTA). Methods All iERM eyes were graded into four stages based on the presence of ectopic inner foveal layers (EIFL) and underwent 23-gauge vitrectomy combined with ERM and internal limiting membrane (ILM) peeling, while their fellow eyes were treated as the control group. OCTA was used to measure retinal thickness(RT), foveal avascular zone (FAZ)-related parameters and superficial and deep capillary plexus (SCP and DCP) layers using 6 × 6 mm scans before, 1 month and 3 months after surgery. In addition, best corrected visual acuity (BCVA), metamorphopsia and macular features were assessed. Results Forty-six subjects were included in this study. In comparison to the preoperative data, visual acuity and metamorphopsia improvement was statistically significant in four stages(P < 0.05) and the higher stage (3 and 4) achieved more pronounced improvements (P = 0.002). For higher stage, RT reduced with an increase in stage(P < 0.001), superficial and deep foveal vessel density (SFVD and DFVD) and parafoveal vessel density (PRVD) in SCP declined remarkably, FAZ area was enlarged obviously, FAZ perimeter (PERIM), foveal vessel density (FD) and PRVD in DCP increased significantly after surgery (P < 0.05). Similar to high-stage patients, those with stage 2 iERMs demonstrated a decreasing trend in central macular thickness (CMT), paraRT (parafoveal thickness), SFVD, and DFVD(P < 0.05). Nevertheless, no notable alterations were observed in other indicators. Distinct from other groups, only CMT and FD increased slightly in stage 1 iERMs (P < 0.05). Post-LogMAR BCVA and LogMAR BCVA-d (pre-LogMAR BCVA –3-month post-LogMAR BCVA) were positively correlated with preoperative stages, CMT, pre-LogMAR BCVA, SFVD, and vascular tortuosity(P < 0.05). but negatively correlated with FAZ area and DFVD (P < 0.05). Preoperative and postoperative metamorphopsia had a certain positive correlation with preoperative CMT (P < 0.05). Conclusions According to OCTA analysis, different EIFL stages of iERMs showed significantly functional and anatomic differences before and after membrane peeling. Low-stage patients have better post-op visual function, while high-stage patients benefit more from surgery. It also demonstrated EIFL staging system contribute doctors to manage iERMs.